2021
DOI: 10.5607/en21007
|View full text |Cite
|
Sign up to set email alerts
|

The Pathological Role of Astrocytic MAOB in Parkinsonism Revealed by Genetic Ablation and Over-expression of MAOB

Abstract: The cause of Parkinson’s disease has been traditionally believed to be the dopaminergic neuronal death in the substantia nigra pars compacta (SNpc). This traditional view has been recently challenged by the proposal that reactive astrocytes serve as key players in the pathology of Parkinson’s disease through excessive GABA release. This aberrant astrocytic GABA is synthesized by the enzymatic action of monoamine oxidase B (MAOB), whose pharmacological inhibition and gene-silencing are reported to significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…We also previously demonstrated that reactive astrocytes excessively express both GFAP and GABA in the SNpc of PD animal models, while normal astrocytes do not [ 11 ]. GFAP and GABA have also been well documented as prominent markers for reactive astrocytes in various brain regions [ 12 , 15 , 16 , 20 , 23 - 25 ]. Therefore, we investigated if the severe PD-like symptoms of the A53T+Adeno group are associated with reactive astrogliosis by performing immunofluorescence staining with antibodies against TH, GFAP, and GABA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also previously demonstrated that reactive astrocytes excessively express both GFAP and GABA in the SNpc of PD animal models, while normal astrocytes do not [ 11 ]. GFAP and GABA have also been well documented as prominent markers for reactive astrocytes in various brain regions [ 12 , 15 , 16 , 20 , 23 - 25 ]. Therefore, we investigated if the severe PD-like symptoms of the A53T+Adeno group are associated with reactive astrogliosis by performing immunofluorescence staining with antibodies against TH, GFAP, and GABA.…”
Section: Resultsmentioning
confidence: 99%
“…The astrocytic GABA has been reported to tonically inhibit neighboring dopaminergic neurons in SNpc, leading to TH loss, dopamine deficiency, and parkinsonian motor deficits [ 11 ]. The excessive GABA from reactive astrocytes has been implicated in various brain diseases accompanying neuroinflammation, including Alzheimer’s disease, stroke, epilepsy, and inflammatory cytokine-induced anxiety [ 12 , 15 , 16 , 20 , 23 - 25 ]. In all these disease conditions, the excessive astrocytic GABA tonically inhibits the neighboring neurons leading to the relevant functional deficits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopaminergic neurons in the substantia nigra are surrounded by astrocytes containing high levels of MAO-B [37]. In the mice model of Parkinson's disease, MAO-B overexpression in astrocytes exacerbated Parkinsonian motor dysfunction, in comparison to wild-type mice [38]. In addition, MAO-B, while less abundant than MAO-A, is also present in dopaminergic neurons of the substantia nigra, where cytosolic dopamine competes between vesicular monoamine transporters and MAO-B [39].…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampal astrocytes in APP/PS1 transgenic mice contain abundant amount of cytosolic GABA due to the high expression level and enzymatic activity of MAOB which is the main astrocytic GABA-synthetic enzyme [ 8 , 15 - 17 ]. On the other hand, the hippocampal astrocytes of the MAOB-KO mice can barely synthesize GABA due to the deficiency of MAOB [ 17 , 18 ]. To investigate the Best1 distribution at the ultrastructural resolution in these mice, we adopted a cutting-edge microscopic technique, Lattice Structured Illumination Microscopy (SIM) which yields a super optical resolution of ~120 nm [ 19 ].…”
Section: Introductionmentioning
confidence: 99%